Development of a tool to support operationalising water safety plans: experiences from a national water utility in Ghana - David Sheehan; Phillip Fasham; Rory Moses McKeown; Asoka Jayaratne (Journal of Water and Health, 2023)
Since their incorporation into the 2004 version of the World Health Organization's (WHO's) Guidelines for Drinking Water Quality (GDWQ), Water Safety Plans (WSPs) continue to be the pre-eminent process for the delivery of safe drinking water to consumers. WSPs achieve this by prioritising proactive, rather than reactive, management of risks to drinking water quality. Since the use of WSPs was incorporated into the GDWQ, a range of supporting resources have been produced to assist water suppliers in preparing WSPs. Producing a robust WSP is an important first step in the management of risk, but in many cases, the implementation of WSPs presents significant challenges, particularly in relation to the implementation of Module 5 (implementing improvements) and Module 6 (monitoring of control measures). To address barriers to WSP implementation, the Ghana Water Company Limited (GWCL), in a peer-to-peer partnership with two Australian water utilities, developed a pilot WSP implementation strategy for one of the company's drinking water supply systems. One of the outputs of the collaboration was the development of a framework for operationalising water safety planning, which incorporates basic guidance for embedding the WSP within routine operations, in order to ensure the safe management of drinking water. HIGHLIGHTS Demonstration of the benefits of peer-to-peer support to improve operational practice.; Development of an adaptable and scalable operational framework to assist WSP implementation.; Organisational adoption of the operational framework, which facilitates both improved water treatment practice and the monitoring of the effectiveness of control measures.; Operational framework could be used as a checklist when conducting internal and external WSP audits.;